Análise geoambiental como subsídio ao ordenamento territorial do município de Barrocas/BA - Anjos, Adineide Oliveira dos (2020)
Human occupation has become increasingly intense in the spaces. This fact is due to the contemporary way of life, intensified by several factors, such as technological advances, population growth, urban and industrial expansion, which pressure and degrade natural goods. Often this spatial organization lacks elements for territorial planning. Thus, this work aims to analyze the geoenvironmental components of the municipality of Barrocas/BA with a view to zoning and local territorial ordering, valuing the socioenvironmental potential and the conservation of natural resources from a systemic view.The studies developed on the aegis of geoenvironmental conceptions are important tools for obtaining information from the biophysical, socioeconomic and degradation processes in loco, culminating as essential instruments for territorial-environmental planning and municipal management. Thus, the development of this research was guided by the geosystemic method proposed by Bertrand (1972; 2004), which indicates to analyze the constituent elements of the landscape by using the temporal-spatial scale of land use and occupation, embracing the proposal of production of systemic knowledge/full. The municipality under study is part of the Sisal Identity Territory, is inserted in the Bahian semi-arid, geomorphologically in the backcountry Pediplano and is configured as a territory recently established as a federative entity (emancipated in the year 2000), but quite anthropized, due to human activities for meet socioeconomic needs. The choice for the municipality analysis unit stems from the fact that it is a scale of public management of natural resources over the aegis of the municipal government, which is also compatible for the delimitation of geosystems, methodology adopted here. Due to this, the accomplishment of this study made possible to analyze the geoenvironmental conditions, the uses and occupation, the anthropic pressures and the associated impacts. Through the geoenvironmental zoning carried out, it was possible to identify, in the Barrocas municipal lands, two Geosystems (Serra do Barandão and Pedimented Surface) and six geofacies (Conserved structural summit, Dissected structural summit, Surface dissected in hills, Lowered saws, Colluvium-alluvial ramp and an artificially destructured surface). With the (re) knowledge of landscape units, an outline of territorial planning was proposed in order to subsidize more sustainable uses for the lands of the municipality in question. It is noteworthy that the zoning process, whatever it may be, is of great importance, being a powerful instrument providing useful information to the territory management process, and the municipality is the ideal laboratory for its experimentation, as it is a territorial and environmental planning and management scale. Thus, from the analysis of the landscape dynamics in loco, it was verified how intense the anthropogenic action in the territory of Barrocas has been taking place. However, it was found that the environmental systems still resist, being observed that time is allowing the process of regeneration and adaptation of geosystems, keeping them in functionality. Thus, new attitudes and actions need to be put into practice, because on this depends the life of man and the planet, considering that the natural resources are exhaustible. Therefore, it is desired that the population and the public power of Baroque seek more sustainable socioeconomic alternatives in order to promote more effective results, enforcing environmental laws and promoting awareness of the environmental issue.